Entrepreneurial Learning City Regions Delivering on the UNESCO 2013, Beijing Declaration on Building Learning Cities (Springer International Publishing, 2018)
This book proposes an alternative strategy to improve and sustain prosperity, through the creation of an entrepreneurial culture in learning cities or city regions. The edited collection provides insights into how entrepreneurship, education, job creation and social inclusion can be aligned through entrepreneurial learning, in the context of territorial development. With rich and varied contributions from a wide field, including policy makers, entrepreneurs, an investment banker, leaders of universities and councils, the voluntary sector, scientists, educators and students, it reviews and assesses how learning cities and regions may become more prosperous by investing in the development of entrepreneurial skills throughout lifelong learning. Reinforced by examples on developing and retaining entrepreneurial people, this book contributes to our understanding of how entrepreneurial learning can be fostered in different city and city-region contexts. It makes an interesting contribution to the field in terms of mapping out complex issues and testing the practical validity of the concept, while also providing rich and insightful case studies centred on the Welsh experience with entrepreneurial learning city regions. The high quality international contributions demonstrate the new worldwide interest in developing an entrepreneurial culture for the benefit of a city or region, rather than an entrepreneurial mind-set for individual benefit. This fascinating subject will be of interest to many social scientists, policymakers, and practitioners. It will be found especially valuable for professionals involved in economic, inclusive and sustainable city or regional development.